Viscous flows : stretching and shrinking of surfaces - Mehmood, Ahmer (Springer, 2017)
This authored monograph provides a detailed discussion of the boundary layer flow due to a moving plate. The topical focus lies on the 2- and 3-dimensional case, considering axially symmetric and unsteady flows. The author derives a criterion for the self-similar and non-similar flow, and the turbulent flow due to a stretching or shrinking sheet is also discussed. The target audience primarily comprises research experts in the field of boundary layer flow, but the book will also be beneficial for graduate students.
Keywords: Viscous flow.; elektronické knihy; electronic books